Role of Silicon on Plant–Pathogen Interactions - Wang, Min; Gao, Limin; Dong, Suyue; Sun, Yuming; Shen, Qirong; Guo, Shiwei (Frontiers in Plant Science, 2017)
Although silicon (Si) is not recognized as an essential element for general higher plants, it has beneficial effects on the growth and production of a wide range of plant species. Si is known to effectively mitigate various environmental stresses and enhance plant resistance against both fungal and bacterial pathogens; however, the underlying mechanisms are largely unknown. In this review, the effects of Si on plant-pathogen interactions are discussedanalyzed, mainly from on physical, biochemical, and molecular aspects. In most cases, the Si-induced biochemical/molecular resistance during plant-pathogen interactions were dominated as joint resistance, involving activating defense-related enzymes activates, stimulating antimicrobial compound production, regulating the complex network of signal pathways, and activating of the expression of defense-related genes. The most previous studies described an independent process, however, the whole plant resistances were rarely considered, especially the interaction of different process in higher plants. Si can act as a modulator influencing plant defense responses and interacting with key components of plant stress signaling systems leading to induced resistance. Priming of plant defense responses, alterations in phytohormone homeostasis, and networking by defense signaling components are all potential mechanisms involved in Si-triggered resistance responses. This review summarizes the roles of Si in plant-microbe interactions, evaluates the potential for improving plant resistance by modifying Si fertilizer inputs, and highlights future research concerning the role of Si in agriculture.